Characterization of a Salmonella abortus equi phage 4FS1 and its depolymerase - Jianchao Zhao; Jiayu Wang; Can Zhang; Shouzhen Xu; Huiying Ren; Ling Zou; Jing Ma; Wenhua Liu (Frontiers in Veterinary Science)
The significant economic losses caused by S. abortus equi in donkey husbandry have increased interest in exploring the potential of phages and their enzymes as control strategies. In this study, a S. abortus equi phage, designated 4FS1, was isolated from sewage at a donkey farm. Transmission electron microscopy (TEM) revealed a typical icosahedral head and a long, non-contractile tail. It exhibited a short latent period of 20 min and a burst size of 160 plaque-forming units (PFU) per cell. It demonstrated a broad host range, infecting 36 out of 60 salmonella strains, with an optimal multiplicity of infection (MOI) of 0.01 for S. abortus equi S1. The phage titer remained stable at 109 PFU/mL between 37°C and 50°C and exceeded 108 PFU/mL at pH from 5.0 to 10.0. After 1 h of UV exposure, the titer remained at 107 PFU/mL and showed no significant variation across NaCl concentrations from 2.5 to 15%. The genome of phage 4FS1 consists of a 42,485 bp linear double-stranded DNA molecule with a G + C content of 49.07%. Of the 56 predicted open reading frames (ORFs), 32 were functional annotated, with no virulence or drug resistance genes identified. ORF36 was predicted to encode a depolymerase responsible for endorhamnosidase activity. Recombinant expression of the Dpo36 protein in prokaryotes significantly reduced biofilm formation and removal. Combined with healthy donkey serum, Dpo36 inhibited bacterial growth in vitro and enhanced the survival rates of mice infected with S. abortus equi. These findings highlight the promising potential of phages and their depolymerases as novel therapeutic agents against S. abortus equi.